Exploring the roles of social presence practices in enhancing virtual teams performance in the higher education sector in Malaysia - Alkoud, Saleh; Zainudin, Dolhadi; Mhd. Sarif, Suhaimi (Human Resource Management Academic Research Society (HRMARS), 2023)
Many recent studies indicate that the application of virtual teams has increased dramatically in recent years in various businesses and public services such as education as a result of the rapid progress in information and communication technology. The use of virtual teams increased further after the spread of the Covid-19 epidemic. The research problem lies in the contradiction between the increasing use of virtual teams in the field of business and services and the high failure rate in virtual teams, as the factors affecting the success of these teams still need further exploration and research. The importance of this study lies in highlighting the most important factors associated with the success of virtual teams in the field of higher education, as this study contributes to bridging the knowledge gap in previous studies that did not adequately address the performance of virtual teams in the higher education sector.